(untitled) (Princeton, 2016)
Bitcoin and Cryptocurrency Technologies provides a comprehensive introduction to the revolutionary yet often misunderstood new technologies of digital currency. Whether you are a student, software developer, tech entrepreneur, or researcher in computer science, this authoritative and self-contained book tells you everything you need to know about the new global money for the Internet age.
Blockchain
Keywords: Bitcoin,Electronic funds transfers,Chuyển tiền điện tử,Bitcoin